2007
DOI: 10.1002/hipo.20366
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by group 1 metabotropic glutamate receptors of depotentiation in the dentate gyrus of freely moving rats

Abstract: In the hippocampus, synaptic depression of potentiated synapses in the form of depotentiation, or of naive synapses in the form of long-term depression (LTD) is mediated by distinct molecular mechanisms. Activation of group 1 metabotropic glutamate receptors (mGluRs) is critically required for both hippocampal long-term potentiation (LTP) and LTD in vivo, but their involvement in depotentiation is unclear. In this study, we investigated whether this class of mGluRs contributes to depotentiation in freely movin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…This is particularly interesting in light of earlier findings that activation of group I mGluRs in hippocampal neurons leads to excitatory effects and potentiation of NMDA-mediated responses (Conn and Pin, 1997) and that mGluR5 and NMDA work in tandem to regulate synaptic strength and flexibility (De Blasi et al, 2001). The inhibition of TBS-LTP by MPEP found in our study corroborates previous reports showing that inhibition of mGluR5 results in an impairment of hippocampal LTP in rats in vivo and in vitro (Manahan-Vaughan, 1997; Balschun and Wetzel, 2002; Naie and Manahan-Vaughan, 2004; Manahan-Vaughan and Braunewell, 2005; Nagaraja et al, 2005; Kulla and Manahan-Vaughan, 2008), and that mGluR5 knock-out mice have a deficit in CA1-LTP (Lu et al, 1997). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is particularly interesting in light of earlier findings that activation of group I mGluRs in hippocampal neurons leads to excitatory effects and potentiation of NMDA-mediated responses (Conn and Pin, 1997) and that mGluR5 and NMDA work in tandem to regulate synaptic strength and flexibility (De Blasi et al, 2001). The inhibition of TBS-LTP by MPEP found in our study corroborates previous reports showing that inhibition of mGluR5 results in an impairment of hippocampal LTP in rats in vivo and in vitro (Manahan-Vaughan, 1997; Balschun and Wetzel, 2002; Naie and Manahan-Vaughan, 2004; Manahan-Vaughan and Braunewell, 2005; Nagaraja et al, 2005; Kulla and Manahan-Vaughan, 2008), and that mGluR5 knock-out mice have a deficit in CA1-LTP (Lu et al, 1997). …”
Section: Discussionsupporting
confidence: 92%
“…Moreover, these results make mGluR1 a good candidate to study the putative role of DP in certain HC-dependent memory behavioral tasks. As previously reported, mGluR1 activity has a potential role for DP at thalamic input synapses onto the lateral amygdale that underlie fear extinction (Kim et al, 2007) To this end, the ability of group I mGluR inhibition to impair learning (Aiba et al, 1994; Rodrigues et al, 2002; Kulla and Manahan-Vaughan, 2008) might be due to an impairment of LTP (mGluR5) and/or augmented DP, depending on the particular learning protocol. Note that Qi et al (2013) reported that DP induced by novelty exploration is mGluR5-dependent, which is in apparent contradiction to the findings in the present work.…”
Section: Discussionmentioning
confidence: 88%
“…However, eEF2 could function at later time points or regulate other forms of plasticity. For example, HFS of the perforant path can activate metabotropic glutamate receptor mechanisms involved in phenomena such as depotentation, metaplasticity, and homeostatic plasticity (73)(74)(75). Metabotropic glutamate receptor-induced long term depression in the CA1 region of hippocampal slices requires local synthesis of Arc from pre-existing mRNA (76), and this synthesis is mechanistically linked to eEF2 phosphorylation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of this knowledge, i.e. the complex innervation of the dentate gyrus, in most studies only a single, monopolar recording electrode was used (Tanner et al, 2000;Blaise and Bronzino, 2003;Sanberg et al, 2006;Poschel and ManahanVaughan, 2007;Kulla and Manahan-Vaughan, 2008). Thus, also Chaulk and Harley (1998) studied the potentiation of PP-evoked potentials in vivo by iontophoretic application of norepinephrine.…”
Section: Discussionmentioning
confidence: 98%
“…In most preparations a stimulating electrode is lowered into the angular bundle of the PP and a single recording electrode into the granule cell layer of the dentate gyrus or the hilar region of the hippocampus to study the synaptic as well as neuronal firing responses after the induction of a plasticity event such as LTP (e.g. Abraham and McNaughton, 1984;Abraham et al, 1994Abraham et al, , 2006Abraham et al, , 2007Popov et al, 2004;Kulla and Manahan-Vaughan, 2008;Korol and Gold, 2008). In all these preparations a typical waveform of the evoked potentials can be recorded, i.e.…”
Section: Introductionmentioning
confidence: 99%